Blade Tip Leakage Flow and Heat Transfer with Pressure-Side Winglet - A. K. Saha; Sumanta Acharya; Ron Bunker; Chander Prakash (International Journal of Rotating Machinery)
A numerical study has been conducted to explore the effect of a pressure-side winglet on the flow and heat transfer over a blade tip. Calculations are performed for both a flat tip and a squealer tip. The winglet is in the form of a flat extension, and is shaped in the axial chord direction to have the maximum thickness at the chord location, where the pressure difference is the largest between the pressure and suction sides. For the flat tip, the pressure-side winglet exhibits a significant reduction in the leakage flow strength. The low heat transfer coefficient “sweet-spot” region is larger with the pressure-side winglet, and lower heat transfer coefficients are also observed along the pressure side of the blade. For the flat tip, the winglet reduces the heat transfer coefficient locally by as much as 30%, while the average heat transfer coefficient is reduced by about 7%. In the presence of a squealer, the role of the winglet decreases significantly, and a 5% reduction in the pressure loss coefficient is achieved with the winglet with virtually no reduction in the average heat transfer coefficient. On the other hand, the suction-side squealer with constant width winglet shows lower heat transfer (reduction of 5.5%) and pressure loss coefficient (reduction of 26%) than its baseline counterpart.